Using information sources by breast cancer women treated with mastectomy - Masoomeh Latifi; Hatav Ghasemi Tehrani; Nader Alishan Karami; Nilofar Barahmand; Leili Allahbakhshian Farsani (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Awareness of sources of information of mastectomy patients has an important role in accessibility of reliable health information sources, thus, when they get information, they can be effective in the treatment and self-care. The present study aimed to identify the sources of information used by women underwent mastectomy. MATERIALS AND METHODS: The current practical research methodology was qualitative, and research method was conventional qualitative content analysis was performed on 17 patients with breast cancer undergone mastectomy. The sample targeted two hospitals were selected based on criteria of Shaeid Mohammadi and the Persian Gulf and Omid Central chemotherapy in Babdar Abbas. Data were collected by face-to-face semi-structured interviews were conducted in winter 2015. Qualitative content analysis of data was performed at the same time of data collection. RESULTS: Three themes were seemed (medical, interpersonal, and media) sources for explaining the sources of information searching. Subcategories derived from the content of medical (physicians, surgeons, and health workers of health facility centers), interpersonal sources (Family and friends, peers), and media sources (printed, electronic, and Internet). CONCLUSION: Given the importance of information on women underwent mastectomy, and their priority in the use of medical sources, necessitates more attention of health system managers and planners in providing essential information and their accessibility.